Phytochemicals as a Complement to Cancer Chemotherapy: Pharmacological Modulation of the Autophagy-Apoptosis Pathway - Md. Ataur Rahman; Md. Ataur Rahman; Md. Abdul Hannan; Md. Abdul Hannan; Raju Dash; MD. Hasanur Rahman; MD. Hasanur Rahman; Rokibul Islam; Rokibul Islam; Md Jamal Uddin; Md Jamal Uddin; Abdullah Al Mamun Sohag; et al. (Frontiers Media S.A., 2021)
Bioactive plant derived compounds are important for a wide range of therapeutic applications, and some display promising anticancer properties. Further evidence suggests that phytochemicals modulate autophagy and apoptosis, the two crucial cellular pathways involved in the underlying pathobiology of cancer development and regulation. Pharmacological targeting of autophagy and apoptosis signaling using phytochemicals therefore offers a promising strategy that is complementary to conventional cancer chemotherapy. In this review, we sought to highlight the molecular basis of the autophagic-apoptotic pathway to understand its implication in the pathobiology of cancer, and explore this fundamental cellular process as a druggable anticancer target. We also aimed to present recent advances and address the limitations faced in the therapeutic development of phytochemical-based anticancer drugs.